Need Analysis of Maritime English for Cadet on Board at Politeknik Pelayaran Malahayati - Manurung, Fitria Ramadhani; Yuli Pera Fitria (Politeknik Pelayaran Sumatera Barat, 2025)
this study is to examine cadets' maritime English demands during onboard training in order to improve English for Specific Purposes (ESP) instruction in maritime higher education. Given the global character of the shipping sector, efficient communication in English is critical to guaranteeing safety, operating efficiency, and compliance with international legislation. Despite past English education, many cadets struggle to use English in real-world shipboard circumstances, particularly technical paperwork, emergency communication, and conversational encounters with multinational personnel. Data were obtained using a qualitative descriptive method, with cadets, lecturers, and ship mentors participating via surveys, interviews, focus group discussions, and document analysis. According to the findings, cadets must improve their listening, speaking, and reading abilities in order to perform well in real-world marine environments. The study also shows a disparity between present classroom training and the genuine linguistic requirements seen at sea. The study advises that Maritime English courses be changed to include task-based learning, simulated techniques, and realistic materials that represent aboard operations. The study helps to establish a needs-based English for Specific Purposes (ESP) framework that better prepares cadets for the communication demands of their future maritime jobs.